2010
DOI: 10.1007/s10212-009-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

The conflict between on-task and off-task actions in the classroom and its consequences for motivation and achievement

Abstract: The relations between students' value orientations, decisions in conflicts between on-task and off-task actions in the classroom, and experiences of motivational interference following these conflicts were investigated. It was expected that well-being value orientation was positively linked and achievement value orientation was negatively linked to decision for off-task behavior in such conflicts and that the higher students' well-being value orientation, the higher their motivational impairment when deciding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…Values seem especially applicable to such conflict situations in which students have to prioritize between actions, because values are ordered by importance in a system of priorities (Schwartz, 2006). Indeed, Kilian, Hofer, Fries, and Kuhnle (2010) found the extent students value well-being and achievement to be related to the experiences they report during on-and off-task behavior when confronted with action conflict scenarios between those two. Values were conceived as determinants of students' experiences in conflicts.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Values seem especially applicable to such conflict situations in which students have to prioritize between actions, because values are ordered by importance in a system of priorities (Schwartz, 2006). Indeed, Kilian, Hofer, Fries, and Kuhnle (2010) found the extent students value well-being and achievement to be related to the experiences they report during on-and off-task behavior when confronted with action conflict scenarios between those two. Values were conceived as determinants of students' experiences in conflicts.…”
Section: Introductionmentioning
confidence: 91%
“…Cross-sectional studies have shown that these two value orientations were related to the motivational interference students reported in action conflict scenarios between school-related and leisure-type activities (Fries, Schmid, Dietz, & Hofer, 2005;Hofer, Schmid, Fries, Zivkovic, & Dietz, 2009;Kilian et al, 2010). In these studies, value orientations were conceived as determinants of the experience of motivational interference.…”
Section: Values As Determinants and Consequences Of Motivational Intementioning
confidence: 98%
See 3 more Smart Citations